2018
DOI: 10.1080/15476286.2018.1440875
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of eukaryotic elongation factor 1 alpha (eEF1A) by dynamic lysine methylation

Abstract: Lysine methylation is a frequent post-translational protein modification, which has been intensively studied in the case of histone proteins. Lysine methylations are also found on many non-histone proteins, and one prominent example is eukaryotic elongation factor 1 alpha (eEF1A). Besides its essential role in the protein synthesis machinery, a number of non-canonical functions have also been described for eEF1A, such as regulation of the actin cytoskeleton and the promotion of viral replication. The functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 40 publications
1
48
0
Order By: Relevance
“…The methylation of eEF1A is conserved from yeast to humans, suggesting that, akin to histone methylation, a modification network may regulate specific eEF1A functions (Hamey and Wilkins, 2018;Jakobsson et al, 2018a). While several conserved enzymes that methylate different residues on eEF1A have been identified, the KMT responsible for generating methylation of eEF1A at lysine 55 (eEF1AK55me), a modification that is present in humans but not detected in yeast, is not known ( Figure 1A).…”
Section: Identification Of the Orphan Gene Mettl13 As A Candidate Eefmentioning
confidence: 99%
See 1 more Smart Citation
“…The methylation of eEF1A is conserved from yeast to humans, suggesting that, akin to histone methylation, a modification network may regulate specific eEF1A functions (Hamey and Wilkins, 2018;Jakobsson et al, 2018a). While several conserved enzymes that methylate different residues on eEF1A have been identified, the KMT responsible for generating methylation of eEF1A at lysine 55 (eEF1AK55me), a modification that is present in humans but not detected in yeast, is not known ( Figure 1A).…”
Section: Identification Of the Orphan Gene Mettl13 As A Candidate Eefmentioning
confidence: 99%
“…The GTPase eEF1A (eukaryotic elongation factor 1 alpha) is an evolutionarily conserved and fundamental non-ribosomal component of the translational machinery and one of the most abundant proteins found in eukaryotic proteomes (Schuller and Green, 2018). Methylation of eEF1A occurs at several lysine residues, many of which are conserved from yeast to humans (Hamey and Wilkins, 2018;Jakobsson et al, 2018a). Further, it has been suggested that, akin to the extensive role histone methylation plays in chromatin regulation, eEF1A methylation may likewise regulate distinct eEF1A-mediated biology, including translation elongation.…”
Section: Introductionmentioning
confidence: 99%
“…With the realization that ribosomes are major sites of protein methylation, several groups focused on the modifications of the elongation factors that closely interact with the ribosomal protein synthesis machinery (19,67,68). It has been known for many years that lysine residues on elongation factors were modified in both prokaryotes and eukaryotes.…”
Section: Unusual Dual Protein Methyltransferases That May Recognize Bmentioning
confidence: 99%
“…In the last few years, seven protein lysine methyltransferases of the SETdomain and seven beta-strand family have been characterized for most of the known modifications for elongation factors 1A, 2, and 3 in yeast and have been designated Efm1 through Efm7 (5,19,67,68). Yeast Efm1, 3, 4, 5, and 6 all appear to be specific for methylating one particular lysine side chain on one specific elongation factor (19,68). However, Efm2 has been shown to recognize lysine residues on both EF2 and EF3 (5).…”
Section: Unusual Dual Protein Methyltransferases That May Recognize Bmentioning
confidence: 99%
“…An example of the rapid progress that has recently been made are studies of Elongation Factor 1 Alpha (eEF1A), an essential GTPase associated with the translation machinery. Methylation of eEF1a was mapped on several lysine residues (Jakobsson et al, 2018a), and five unique KMTs were recently connected to methylation of eEF1a (Jakobsson et al, 2018b;Liu et al, 2019;Małecki et al, 2017). Two groups independently identified Methyltransferase-like Protein 13 (METTL13) as the KMT responsible for catalyzing dimethylation on lysine 55 of eEF1A (Jakobsson et al, 2018b;Liu et al, 2019).…”
Section: Lysine Methylation Outside the Nucleusmentioning
confidence: 99%